Penerapan ERP Frontaccounting Pada Sistem Pembelian, Penjualan Dan Stok Barang di PT. Laba Usaha Mandiri - Mohamad Firdaus; Indra Bakti (Jurnal Teknologi Informasi (JUTECH), 2023)
PT Laba Usaha Mandiri is one of the start-up companies engaged in the sale of oil palm. The system of purchasing, sales, and inventory of goods is done manually with the help of a computer. However, to record finances and a more controlled business, it is necessary to implement an Enterprise Resource Planning (ERP) application in the company. The results of the application selection analysis show that the FrontAccounting Application is a suitable application for the company. Therefore, the implementation of the application is carried out at the company. after that the system is checked to ensure that the ERP application is appropriate and can run as expected. This test is based on the literature method and the existing business processes at PT Laba Usaha Mandiri. From the test results, it is concluded that ERP is in accordance with the business needs of the company.